Alternative isoforms of BmYki have different transcriptional co-activator activity in the silkworm, Bombyx mori. (November 2019) - Liang, Zi; Lu, Yahong; Jiang, Mengsheng; Qian, Ying; Zhu, Liyuan; Kuang, Sulan; Chen, Fei; Feng, Yongjie; Hu, Xiaolong; Cao, Guangli; Xue, Renyu; Gong, Chengliang
Highlights: At least seven alternative splicing isoforms of BmYki were identified. S 97 phosphorylation contributes to the cellular location of BmYki1. BmYki3 plays a major positive regulatory role in Hippo signaling pathway. BmYki2 plays a role of microregulation and balance in Hippo signaling pathway. BmYki1 plays a secondary positive regulatory role in the Hippo signaling pathway. Abstract: Yorki (Yki), a transcriptional co-activator that is a key component of the Hippo pathway, induces the transcription of a number of targets that promote cell proliferation and survival. Bombyx mori Yki3 (BmYki3), with 445 amino acid residues, facilitates cell migration and cell division, and enlarges cultured cell and wing disc size. In this study, cellular localization, transcriptional co-activator activity, cell migration, cell cycle, and cell size were characterized in alternative isoforms of BmYki. BmYki1 and BmYki3 are mainly located in the cytoplasm and nucleus, respectively, while, BmYki2 is located in both the cytoplasm and nucleus. The mutation BmYki1 S97A (S 97 mutated to A) was transported from the cytoplasm to nucleus. Cell migration, cell cycle, and cell size could be enhanced by BmYki, however, the effect of BmYki1 and BmYki2 on cell proliferation was less compared to BmYki3. Moreover, wing discs could be enlarged by overexpressing BmYki1 or BmYki2 isoforms. Dual-luciferase reporter assay showed that BmYki3 had the highest activity to B. mori ovarian tumor gene. In BmN cells overexpressing one of the BmYki isoforms, expression levels of kibra ortholog ( kibra ), inhibitor of apoptosis protein ( iap ), four-jointed ( fj ), expanded ( ex ), crumbs ( crb ) and BMP and activin membrane-bound inhibitor homolog ( Bmpr ) genes were upregulated, while those of α-catenin ( α-cat ), decapentaplegic ( dpp ), serrate ( serr ) and signal transducer and activator of transcription ( stat ) genes were down-regulated. There was some difference in the regulation of gene expression between different isoforms. These results suggested that the activity of BmYki isoforms was different in the silkworm.